Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
https://doi.org/10.13016/M2QR4NT6S
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Saphisme et décadence dans Paris fin-de-siècle - Albert, Nicole G. (La Martinière, 2005)
Figures emblématiques des années 1900, les saphistes sont associées aux premiers balbutiements d'un féminisme qui dérange et qui, par réaction, nourrit d'inépuisables fantasmes. Objets de scandale ou héroïnes, elles inspirent artistes et poètes. C'est l'ensemble de ces représentations ambiguës qui sont ici analysées.
Keywords: 1800-1899; approches et analyses; arts; corps; discipline; discours dominant; europe; france; lesbianisme; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; études littéraires

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." – Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Macmillan, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques